Analisis Faktor yang Berhubungan dengan Kejadian Rest Placenta di RSUD Patuh Patut Patju Lombok Barat - Baiq Dika Fatmasari; Eka Mustika Yanti; Fuji Indriani Rahayu (An-Najat, 2023)
Retention of retained placenta or commonly known as rest placenta is one of the important problems in obstetrics which causes maternal bleeding during labour. This increases perinatal and maternal morbidity and mortality. There are several causative factors that are suspected of causing retained placenta., namely age, parity, anemia status, history of abortion and history of induction of oxytocin drip. Aim: To find out the factors associated with the incidence of Rest placenta at Patut Patju West Lombok Hospital. Method:This research is a quantitative analytic research study with the Cohort Retrospective method (retrospective study), namely research conducted by observing the data that has been collected and is a type of research that has the same objectives and indicators as the type of prospective cohort research.. The research method used in data collection techniques namely, secondary data from the patient register data which is the data of all mothers giving vaginal birth at Patut Patuh Patju Hospital in a period of 5 years (January 2018-October 2022), 4,498 samples taken using the systematic random sampling technique with intervals of 12 obtained a total of 367 samples. Results: At the Patut Patuh Patju Hospital in West Lombok district, as many as 367 samples were taken, there were 41 or 11.2% of cases of rest placenta. The number of cases of rest placenta at the age of <20 and > 35 years was 26 people or 31%. The number of cases of rest placenta in multi and grande parity was 27 people or 12%. The number of cases of rest placenta with anemia status was 9 people or 9.3%. The number of cases of rest placenta with a history of abortion was 19 people or 7.1%, and the number of rest placentas with a history of termination of oxy drip was 22 people or 14%. Conclusion: There are several factors that have a significant relation with the incidence of rest placenta, including age, anemia status, and abortion. Meanwhile, the parity factor and history of oxytocin drip did not have a significant relationship with the incidence of rest placenta.